BESAR MASALAH DAN HUBUNGAN DISABILITAS DENGAN PENYAKIT KRONIS DAN GANGGUAN MENTAL EMOSIONAL BERDASARKAN SURVEI KESEHATAN NASIONAL RISKESDAS 2007 - 2008 - Isfandari, Siti (Media Penelitian dan Pengembangan Kesehatan, 2009)
Information about prevalence, mortality and disability is necessary for resource allocation in health sectors. This analysis focuses on the magnitude of disability and its association with chronic disease and emotional distress. There are 664197 records can be analyzed. Prevalence of disability is 31.2% (95% CI = 30.9 -31.5). The results showed that age is the strongest contributors of disability, followed by psychological distress and stroke. This result pointed out the importance that health service sector should pay attention on the psychological aspects of patients. Key words : Disability, Emotional, Prevalence